2016
DOI: 10.1186/s40064-016-2694-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical study of rotational micromovement of the pedicle screw

Abstract: BackgroundIn regard to the fixation using a pedicle screw (PS) and rod system, the mechanism from the onset of the clear zone up to the development of loosening of the pedicle screw is not completely clarified. The purpose of this study is to determine the cause of the pedicle screw loosening by performing a biomechanical study with three-dimensional movie analysis.MethodsTen PS fixation model of the lumbar spines (L3–4) of boar cadavers were used. The rotational angles of the L3 and L4 vertebral body and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…12,13 On the other hand, the most reliable mechanisms of screws loosening were considered cyclic caudocephalad toggling and rotational stress causing micromovements between vertebral body and screws that may finally resulted in the screws loosening. 29 After the bilateral facet joints removal an additional rotational stress at the interface of bone and screw was expected, finally resulting in an increased rate of loosening. Even though the effect of bilateral facet joints removal was statistically significant, the relative influence was small.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 On the other hand, the most reliable mechanisms of screws loosening were considered cyclic caudocephalad toggling and rotational stress causing micromovements between vertebral body and screws that may finally resulted in the screws loosening. 29 After the bilateral facet joints removal an additional rotational stress at the interface of bone and screw was expected, finally resulting in an increased rate of loosening. Even though the effect of bilateral facet joints removal was statistically significant, the relative influence was small.…”
Section: Discussionmentioning
confidence: 99%
“…However, loosening of screws may occur during the early postoperative period (< 6 months) [14]. Mizuno et al reported that rotational micromovement occurs between the PS and the vertebral body, and repeated rotational micromovements might cause loosening of the screw [15]. We hypothesized that the displacement of the screw in the vertebra might occur rst through screw loosening.…”
Section: Discussionmentioning
confidence: 95%
“…According to the results of research on biomechanics, the most reliable mechanism of PSL are micro-movements caused by craniocaudal toggling and rotational stress that increase the load to the zone of the bone-screw interface ( 29 ). To minimize micro-movements that cause PSL the application of the most stable type of fusion is required.…”
Section: Discussionmentioning
confidence: 99%